Assessing Motorcyclists Risky Riding Behaviour At Three-Legged Stop-Controlled Junctions - Shee, Tian Hao (Universiti Sains Malaysia, 2021)
The study was done to determine the motorcyclist risky riding behaviour at conventional and unconventional T-junction. Type A T-junction is a typical T-junction, while Type B unconventional T-junction with a short lane exclusively for right-turning from major road and short merging lane on the receiving approach on major road to act as the exit lane for a vehicle making right turn from minor road and Type C unconventional T-junction with an exclusive right turn exit lane from major road and a short merging lane on the receiving approach on major road which acts as the exit lane for the through movement from the major road. Based on-site data collection, in general, there are eight risky riding behaviour of motorcyclists determined, which are “RB1-riding motorcycle without wearing helmet”, “RB2-no signal when turning”, “RB3-not switching on the headlight during daytime”, “RB4-riding on the opposite or wrong side of road”, “RB5-crossing a junction without fully stopping”, “RB6-riding or performing a turn that is not according to the right of rule”, “RB7-stop after the stop line” and “RB8-playing mobile phone”. Based on the discussions, Type A conventional T-junction has the highest percentage of motorcyclists with risky behaviour. Still, it is the safest junction among the three types of junctions. Based on the findings of this study, although Type A conventional T-junction has the highest percentage of motorcyclists with risky behaviour, but it is the safest junction. Those risky riding behaviours commonly performed by the motorcyclists have a lower consequence as compared with other risky riding behaviour like “RB5-crossing a junction without fully stopping” which will bring serious consequences to the road users. This is because motorcyclists crossing a road without fully stopping is one of the most dangerous situations at the T-junction, it will affect the hierarchy of the right of way at T-junction and it will danger other road users. Apart from that, Type B unconventional T-junction showed the best performance. Based on “RB5-crossing a junction without fully stopping”, it has revealed that the motorcyclists at Type B junction are very aggressive when making a right turn either from major or minor road. Although this risky riding behaviour has undeniable consequences to the road users, it has also shown that the motorcyclists at Type B unconventional T-junction have relatively high confidence when crossing the junction by clearing the conflict area.